PWE-123 Adaptive immune responses in ALF. (22nd June 2015) - Khamri, W; Anderson, AE; Abeles, RD; Auzinger, G; Bernal, W; Willars, C; Robinson, JH; Lombardi, G; Thursz, MR; Wendon, J; Antoniades, CG
Abstract : Introduction: Acute liver failure (ALF) is characterised by an overwhelming hepatic necrosis, imuneparesis and susceptibility to infections. To date, a number of defects in innate immune responses have been identified but defects in adaptive immune responses remain unexplored. The aims of this study were to evaluate whether impairment in adaptive immune responses could also account for the immuneparesis and infection susceptibility in ALF. Method: CD4 + T-cell-subsets in peripheral blood mononuclear cells (PBMCs) from 20 ALF patients and 10 healthy controls (HC) were determined using multicolor flow cytometry. CD45RA/RO were used to differentiate naïve and memory CD4 + T-cells. Expression or lack of expression of CD45RO/CCR7 was used to determine effector memory (TEM ) subset. Negative regulators of T cell activation (CTLA-4) were analysed. Specific CD4 + T-cell antigen-recall responses to a pool of HLA class II-restricted T cell epitopes were examined in vitro in the presence or absence of anti-CTLA-4 blocking antibody. CD4 + T-cell proliferation was assessed by flow cytometry and IL-2 secretion by ELISA. Soluble CTLA-4 (sCTLA-4) in sera samples were measured using ELISA. Results: Whilst overall percentages of circulating CD4+ T lymphocytes were expanded in ALF (p=0.03), we report a significant reduction in the frequency of memory CD4 + T-cell population (p=0.01). MELD score correlated negatively with the proportion of CD4 + T-cells (r=-0.462, p=0.06). Furthermore, TEM population was significantly reduced in ALF in comparison to HC (p=0.04). This reduction was highly significant in patients with a poor outcome (p=0.002). CTLA-4 expressing CD4 + T-cells were significantly higher in ALF compared to HC (p=0.0001). Similarly, levels of sCTLA-4 in the sera of ALF were significantly elevated (p= 0.02). ALF (n = 4) showed a defect in proliferative responses to recall antigens compared to HC (n = 3) (p = 0.05). However, blockade of CTLA-4-4 was sufficient to restore antigen-recall responses defined by increased T cell proliferation (p=0.05) and IL-2 secretion (0 vs 20.84 pg/ml). Conclusion: Our novel data identify defects in function of circulating CD4 + T-cell subsets in ALF with a significant increase in the CTLA-4 expressing CD4 + T-cells, a phenotype with an inhibitory functional aspect. Proof-of-principle experiments indicate that blocking CTLA-4, a crucial immune checkpoint, may be a promising immunotherapeutic target to boost adaptive immune responses and reduce susceptibility to infection in ALF patients. Disclosure of interest: None Declared.